Floral Transcriptome Sequencing for SSR Marker Development and Linkage Map Construction in the Tea Plant (Camellia sinensis) - Tan, Li-Qiang (Public Library of Science, 2013)
Despite the worldwide consumption and high economic importance of tea, the plant (Camellia sinensis) is not well studied in molecular biology. Under the few circumstances in which the plant is studied, C. sinensis flowers, which are important for reproduction and cross-breeding, receive less emphasis than investigation of its leaves or roots. Using high-throughput Illumina RNA sequencing, we analyzed a C. sinensis floral transcriptome, and 26.9 million clean reads were assembled into 75,531 unigenes averaging 402 bp. Among them, 50,792 (67.2%) unigenes were annotated with a BLAST search against the NCBI Non-Redundant (NR) database and 10,290 (16.67%) were detected that contained one or more simple sequence repeats (SSRs). From these SSR-containing sequences, 2,439 candidate SSR markers were developed and 720 were experimentally tested, validating 431 (59.9%) novel polymorphic SSR markers for C. sinensis. Then, a consensus SSR-based linkage map was constructed that covered 1,156.9 cM with 237 SSR markers distributed in 15 linkage groups. Both transcriptome information and the genetic map of C. sinensis presented here offer a valuable foundation for molecular biology investigations such as functional gene isolation, quantitative trait loci mapping, and marker-assisted selection breeding in this important species.